1978
DOI: 10.1161/01.res.43.4.553
|View full text |Cite
|
Sign up to set email alerts
|

Role of the peripheral vasculature in changes in venous return caused by isoproterenol, norepinephrine, and methoxamine in anesthetized dogs.

Abstract: SUMMARY We studied effects on venous return of a-and /8-adrenergic agonists in anesthetized dogs. Blood from the superior and inferior venae cavae (venous return) was drained at the level of the tricuspid valve into a reservoir, from which blood was pumped into the right atrium at a constant rate. Isoproterenol infused into the ascending aorta or the right atrium increased the venous return and heart rate and decreased systemic blood pressure. The increase in venous return produced by isoproterenol given into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
1

Year Published

1980
1980
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(41 citation statements)
references
References 20 publications
2
38
1
Order By: Relevance
“…The opposite effect, i.e., relaxation after a prolonged increase in distending pressure (delayed compliance or viscoelastic creep), may be significant (358). By decreasing venous resistance due to relaxation of sphincters, e.g., in the hepatic vein, ,8-aclrenergic stimulation may centrally displace venous volume (163).…”
Section: Dynamic Responses To Posture Changesmentioning
confidence: 99%
“…The opposite effect, i.e., relaxation after a prolonged increase in distending pressure (delayed compliance or viscoelastic creep), may be significant (358). By decreasing venous resistance due to relaxation of sphincters, e.g., in the hepatic vein, ,8-aclrenergic stimulation may centrally displace venous volume (163).…”
Section: Dynamic Responses To Posture Changesmentioning
confidence: 99%
“…It has been suggested that there may be a sphincter mechanism regulating hepatic venous outflow (Knisely, Harding & Debacker, 1957;Greenway & Oshiro, 1973). However, the only physiological evidence in support of this has been indirect and has shown hepatic outflow to be influenced by various humoral stimuli (Imai, Satoh & Taira, 1978;Rutlen, Supple & Powell, 1981;Rothe, Flanagan & Maass-Moreno, 1990). No information was provided on where any potential site of obstruction to flow may have been.…”
Section: Introductionmentioning
confidence: 99%
“…By using the open loop method, we have recently gained some insight into the role of vascular a and ;3 adrenergic receptors in changes related to venous return produced by sympathomimetic amines (12). In the present study in addition to nitroglycerin, 3 vasodilators, i.e., verapamil, trimetazidine, and 3,5-dicarbethoxy-2,6-dimethyl-4-(2-trifluoromethyl-phenyl)-1,4-dihydro pyridine (SK&F 24260) (13,14) were used, since in the previous studies (7,8) …”
mentioning
confidence: 99%